Bifosfonat Kullanımına Bağlı Olarak Maksillada Kemik Nekrozu Oluşumu: Bir Olgu Sunumu - Adnan Ozturk; Kaan Orhan; Durmus Ilker Gorur; Aysegul Mine Tuzuner Oncul; sila sahin (Cumhuriyet University, 2011)
<!--[if gte mso 9]> Normal 0 21 false false false TR X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> &